Elder men's bromance in Asian lands: normative Western masculinity in Better Late than Never. Issue 4 (8th August 2018) - Oh, David C.
ABSTRACT: Better Late than Never is a remake of a Korean reality T.V. travel show, which aired on N.B.C. in August 2016. The show's premise features four elder celebrity men – Henry Winkler, William Shatner, Terry Bradshaw, and George Foreman – with their mid-30s companion Jeff Dye as they travel through the "exotic" lands of East Asia. Through the use of two popular narrative tropes, the bromance and the Western journey for self-discovery in Asia, the show argues that the interaction with the Asian other is beneficial primarily in masculine self-discovery and masculine homosocial bonding. Borrowing from Steeves's use of the hybrid encounter, I argue that B.L.T.N. positions the strange Asian other as valuable only as a reference for becoming reacquainted with the U.S. American self and emotionally connected to his fraternal companions. Thus, B.L.T.N. rejects hybridity and reinforces U.S. American masculinity through the reification of ideologically preferred contact with the other that is shallow and that benefits the Western traveler.